A novel type of composite LTCC material for high flexural strength application. Issue 2 (February 2021) - Qin, Tianying; Zhong, Chaowei; Tang, Bin; Zhan, Shuren
Abstract: A novel high flexural strength Low-temperature co-fired ceramic (LTCC) material, x Al2 O3 + (1- x ) BaO-Al2 O3 -SiO2 -B2 O3 -ZnO-CaO-MgO ( x = 35−50 wt. %) glass-ceramics, was synthesized by conventional solid-state reaction method. The activation energy, phase assemblage, thermal properties, mechanical properties, chemical compatibility with Cu and microwave dielectric properties of the prepared samples were discussed. The composites ( x = 35−50 wt. %) could be densely sintered at 950 °C/2 h. With the content of Al2 O3 increasing, the coefficient of thermal expansion ( CTE ) increases from 6.7 × 10 −6 /K to 7.2 × 10 −6 /K, and the flexural-strength first increases from 280 to 360 MPa, and then decreases from 360 to 240 MPa. The x Al2 O3 + (1- x ) BaO-Al2 O3 -SiO2 -B2 O3 -ZnO-CaO- MgO ( x = 35−50 wt. %) glass-ceramics sintered at 950 °C for 2 h has the excellent dielectric properties and mechanical properties at x = 45 wt. %: εr = 7.6, tanδ = 3.01 × 10 -4 at1 MHz, τf =-35.25 ppm/ °C, CTE = 6.79 × 10 −6 / °C, flexural strength = 360 MPa.